IMPACTS OF A SINGLE SESSION OF TRANSCRANIAL DIRECT CURRENT STIMULATION COMBINED WITH PROPRIOCEPTIVE EXERCISES ON GAIT IN CHILDREN WITH VISUAL IMPAIRMENT: A CASE STUDY (CIPEEX, 2025)
Loss of vision promotes various alterations in the sensorimotor system, requiring the activation of neuroplasticity in the central nervous system. This excitation, combined with transcranial stimulation, aims to induce more effective modulations and adaptations in gait. Objectives: This study aims to identify the effects of a single session of transcranial direct current stimulation combined with proprioceptive exercises on the spatiotemporal parameters of gait in children and pre-adolescents with visual impairment. Methods: This is a case study involving a 10-year-old child with moderate visual impairment. The sample was referred by the Municipal Center for Diversity Care (CEMAD) in Anápolis. Initially, the sample underwent a screening process using a child identification form to analyze all inclusion and exclusion criteria. Subsequently, the participant underwent evaluations at UniEVANGÉLICA in the Human Movement Analysis Laboratory (LAAMH). Results: The results obtained from comparing spatiotemporal parameters before and after the intervention showed no statistical differences only in speed and absolute step length. Conclusion: Thus, the visually impaired child evaluated generally exhibited significant differences in nearly all assessed parameters.
Keywords: Transcranial stimulation; Proprioception; Gait; Children; Visual impairment